The DECADE learning model: Integrating learning theories in mathematics education - Putra, Fredi Ganda; Sutiarso, Sugeng; Nurhanurawati, Nurhanurawati; Hariri, Hasan; Caswita, Caswita; Maulina, Dina (Indonesian Journal of Science and Mathematics Education, 2026)
Mathematics education has long been influenced by diverse learning theories that are frequently applied in isolation, leading to theoretical fragmentation in instructional design. This study addresses that gap by proposing the DECADE learning model as a theoretically integrated framework that systematically synthesizes cognitivism, constructivism, information processing theory, dual coding theory, and cognitive load theory within a coherent instructional architecture. The study aims to establish the epistemological foundation and structural validity of this multi-theory integration in the context of mathematics education. Employing a mixed-method developmental design, qualitative thematic analysis was conducted to map the five theoretical foundations into a progressive six-phase instructional structure, followed by quantitative expert judgment to assess content and construct validity. The results demonstrate strong conceptual stability, with mean validity indices exceeding 90% of the ideal score, indicating high alignment between theoretical rationale, instructional syntax, and structural coherence. Rather than claiming empirical effectiveness, this study confirms the theoretical and structural feasibility of DECADE as an expert-validated framework. The findings contribute to mathematics education by offering a principled synthesis that bridges constructivist meaning construction and cognitive regulation, thereby providing a consolidated theoretical foundation for future empirical investigation and instructional innovation.